Values and ideology in place descriptions in geography schoolbooks: the Israeli case - Bar-Gal, Yoram (ERDKUNDE, 2000)
The ideology which shaped the education system, buried its values in textbooks and curricula. Therefore in order to understand the various changes in ideology one must turn to language, which transmits the ideological meanings within a certain period. Textbooks provide social manifestoes, which include the formal language in which ideology is used for purposes of communication and socialization. Geography textbooks, as other social archetypes, may be used as raw material for the purpose of understanding the culture which creates them. As raw material, the culture which writes the textbooks lies hidden within them, and these texts create images crucial for the culture's survival. From the examples discussed in this article, one can see that geography textbooks present different representations of the same places. One can see that the representation of places in geography textbooks (which influence the construction of a student's spatial conception) is a direct result of the accepted ideology. In this way, the educational system, which is an extension of the prevailing political power, may insure continuity and survival of its ideological perception of space and places within a country.